The Centrality of Customary Law in the Judicial Resolution of Disputes that Emanate from it – Dalisile v Mgoduka (5056/2018) [2018] ZAECMHC - Nomthandazo Ntlama (Obiter, 2019)
The recent judgment by the Mthatha High Court in Dalisile v Mgoduka ((5056/2018) [2018] ZAECMHC (Dalisile)) has elicited much jubilation over the permeation of customary-law principles into the judicial resolution of disputes that emanate from a customary-law context. The judgment comes at a time when common-law principles appear to have infiltrated the resolution of disputes that originate from customary law. This case paves the way and provides a foundation for the resolution of customary-law disputes within their own context. It reinforces arguments that have long been canvassed to constitutionalise customary law within its own framework. It endorses the envisioned commitment to translate into reality the “healing of the divisions of the past” as envisaged in the preamble of the Constitution of the Republic of South Africa 1996. Section 211(3) of the Constitution is distinct and prescriptive on the obligations of the courts relating to the application of customary law. Section 211(3) is in the context of pursuing the advancement of a constitutionalised system of customary law that seeks to equate the applicable laws of the Republic.This case has filled a lacuna in the application and interpretation of customary law, which has been clouded by the prism of common law. The gap was acknowledged by the court in Alexkor Ltd v Richtersveld Community (2003 (12) BLCR 1301 (CC).In Alexkor, customary law was affirmed as an independent and legitimate source of law that is empowered to regulate its own affairs within the framework of the Constitution. It does not have to be legitimised and validated by common-law principles in addition to the Constitution.Resolving disputes arising from customary law has been a great cause for concern. The courts have delivered many disappointing judgments in the area of resolving customary-law disputes. These judgments appear to lean towards importing common-law principles into the resolution of disputes that arise from the system of customary law. This case note does not intend to discuss these judgments in any depth as they have been dealt with elsewhere.It is thus not the purpose of this case discussion to delve into the history of customary law. Its intended focus is limited to the significant stride made by the court in Dalisile in uprooting the dominance of the application of common-law principles in the resolution of disputes that arise from the system of customary law. The objective is to generate debate on the contribution that the judgment makes to the incorporation of Africanised principles into the broader constitutional framework of the jurisprudence of our courts. The note argues that it is the Constitution that is the dominant authority over all the legal systems that are applicable in the Republic, including customary law.